Entry of men into the labour market in West Germany and their career mobility (1945-2008) - Rolf Becker; Hans-Peter Blossfeld (Journal for Labour Market Research, 2017)
This study analyses how the long-term modernisation process as well as ups and downs of business cycles affect the entry of men into the labour market in West Germany and their career mobility. Combining longitudinal data from the German Life History Study and the ALWA study, we first reconstructed men's job histories continuously for the period between 1945 and 2008. As a measure of men's 'goodness of jobs' at entry into the labour market and across the job career, the magnitude prestige scale (MPS), has been employed. Then, we used the time series data obtained from official statistics to perform factor analysis and suggest a more substantially grounded approach than the conventional approach to the analysis of age (A), period (P) and cohort (C) effects. In particular, we assessed how the modernisation process and continuously changing labour market conditions affect men's entry into the labour market across successive cohorts. Based on their further occupational careers, we used a multi-level event-history model to study how placements in first jobs (cohort effect) and the continuously changing macro structure (period effect) influence men's upward, lateral, and downward career mobility, controlling for men's individual-level resources, such as educational attainment and changing labour force experience (life-course or age effect). This fully dynamic analysis shows that there was improvement in the quality of entry-level jobs and increased mobility across men's birth cohorts. This allows us to gain a better understanding of how long-term macroeconomic trends have influenced social inequality in West Germany across several generations. – – In dieser Studie wird untersucht, wie der langfristige Modernisierungsprozess und der Verlauf der Konjunkturzyklen sowohl den Arbeitsmarkteintritt von westdeutschen Männern als auch ihre Karrieremobilität beeinflusst. Mittels kombinierter Längsschnittdaten der Deutschen Lebensverlaufs- und der ALWA-Studie werden zunächst deren Karriereverläufe für die Periode von 1945 bis 2008 rekonstruiert. Für die Messung von Erfolgen beim Berufseintritt und in der Karriere wird die Magnitude-Prestige-Skala (MPS) herangezogen. Dann werden Zeitreihendaten der amtlichen Statistik herangezogen, um eine Faktorenanalyse durchzuführen, deren Ergebnisse dazu verwendet werden, in einer alternativen Art und Weise Alters-, Perioden- und Kohorteneffekte für Mobilitätsprozesse aufzudecken. Es wird für aufeinander folgende Geburtskohorten überprüft, wie sich Modernisierungsprozess und kontinuierlich verändernde Arbeitsmarktbedingungen auf den Berufseintritt auswirken. Für die weiteren Berufsverläufe wird ein dynamisches Mehrebenen-Modell verwendet, um zu untersuchen, wie die Platzierung im ersten Job (Kohorteneffekt) und die sich kontinuierlich verändernden Makrostrukturen (Periodeneffekte) die Auf- und Abwärtsmobilität sowie die laterale Mobilität unter Kontrolle individueller Ressourcen wie etwa Bildung und Berufserfahrung (Lebenszyklus- bzw. Alterseffekt) beeinflussen. Diese dynamische Analyse zeigt, dass sich in der Kohortenabfolge die Qualität der Einstiegsbeschäftigungen verbessert und die Karrieremobilität zugenommen hat. Sie deckt auf, wie langfristige makroökonomische Trends die soziale Ungleichheit in Westdeutschland über verschiedene Generationen strukturieren.
Keywords: 330; APC analysis; Labour market entry; Career mobility; Modernisation process; Business cycles